2020
DOI: 10.3390/ani10071202
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers to Implementing Pain Management for Piglet Castration: A Focus Group of Swine Veterinarians

Abstract: Surgical castration is a painful husbandry procedure performed on piglets in the United States (US) to improve meat quality. Veterinarians play a crucial role in developing pain management protocols. However, providing pain management for castration is not common practice in US swine production systems. Therefore, the objective of the present study is to identify factors influencing swine veterinarian decision-making in regard to pain management protocols for piglet castration using focus group methodologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In a 2017 report by Moggy et al [ 69 ], a robust majority of surveyed cattle producers either ‘Strongly agreed’ or ‘Somewhat agreed’ that castration (70%) and disbudding (85%) procedures are painful. However, this and similar works also identified medication cost as a substantial barrier to producers providing pain management on-farm [ 7 , 69 ] and this challenge persists across livestock production industries [ 70 ]. Despite its practicality, the pharmacokinetic properties of aspirin also remain underreported and not well characterized in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…In a 2017 report by Moggy et al [ 69 ], a robust majority of surveyed cattle producers either ‘Strongly agreed’ or ‘Somewhat agreed’ that castration (70%) and disbudding (85%) procedures are painful. However, this and similar works also identified medication cost as a substantial barrier to producers providing pain management on-farm [ 7 , 69 ] and this challenge persists across livestock production industries [ 70 ]. Despite its practicality, the pharmacokinetic properties of aspirin also remain underreported and not well characterized in cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, changes to analgesic use by veterinarians may not result in large scale actionable changes in pain management on-farm [ 34 ] given only 32.2% of producers have increased analgesic use over the past ten years. Although veterinarians are viewed by producers as valuable resources in regards to animal health and welfare, the producer most often performs daily decision-making specific to animal care and treatment [ 35 ]. Therefore, the willingness of the producer to implement pain management protocols will likely have a greater impact on individual animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is not unique to cattle veterinarians in the US alone. Wagner and colleagues [ 35 ] conducted a similar study assessing the perspective of swine veterinarians on implementing pain management for piglets and identified that the lack of approved products validated for efficacy is one of the main concerns to implementing pain management on swine farms.…”
Section: Discussionmentioning
confidence: 99%
“…However, no current studies to date have assessed actual implementation of pain relief on-farm, and older studies dating back to 2016 noted only 5% of male piglets in some European countries are castrated with pain relief [ 12 ]. Currently, the US has no Food and Drug Administration (FDA) approved drug specifically labelled for pain management in swine if veterinarians were mandated to provide pain control [ 1 , 13 ]. In order to obtain FDA approval for the use of pain relief in pigs, a product must first demonstrate efficacy as supported through clinically validated end-points [ 1 ].…”
Section: Introductionmentioning
confidence: 99%